2020
DOI: 10.26464/epp2020044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stratospheric evolution during the major sudden stratospheric warming events in 2018 and 2019

Abstract: The longitudinal dependencies of the temperature-enhanced regions are related to the distribution of anticyclones in the prewarming period q The polar vortex underwent recombination in the 2018 sudden stratosphere warming event (SSW) but splitting in the 2019 SSW in the postwarming period q Transitions of the polar vortices were all observed over the Atlantic region in the postwarming period q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…It is quasi-stationary wave 2 that was responsible for the splitting of the polar vortex in SSW 2018, in consistency with other studies (e.g. Ma et al, [14] 2020), and the manifestation of this large-scale polar process was observed in the midlatitudes. This is not surprising, since from the mid-February, zonal wind reversal to the easterlies expanded into the extratropics forming the stratospheric easterly layer between the polar and tropical latitudes (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is quasi-stationary wave 2 that was responsible for the splitting of the polar vortex in SSW 2018, in consistency with other studies (e.g. Ma et al, [14] 2020), and the manifestation of this large-scale polar process was observed in the midlatitudes. This is not surprising, since from the mid-February, zonal wind reversal to the easterlies expanded into the extratropics forming the stratospheric easterly layer between the polar and tropical latitudes (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The vertical structure of the polar vortex determines the propagation of the planetary waves (Rossby waves) that penetrate into the middle atmosphere from the troposphere [4][5][6][7][8]. At high activity of planetary waves, the polar vortex is weakening or even change the zonal wind direction from westerly to easterly, when sudden stratospheric warming (SSW) event is observed [9][10][11][12][13][14] and the destruction of the vortex is accompanied by a sharp increasing of the polar stratosphere-mesosphere temperature [1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Negative temperature anomalies were strongest (about -30K) in the initial SSW phase (10-20 February, purple in Figure 4). This is consistent with the splitting of the polar vortex and the displacement of the larger vortex part to the western hemisphere (around 90 • W) [12][13][14].…”
Section: Figure 4asupporting
confidence: 87%
“…The onsets of the recent Arctic SSW events in 2018 and 2019 were associated with vortex split and vortex displacement due to the dominance of wave 2 and wave 1, respectively [12][13][14]. Along with the altitude and time variation of the amplitude, wave 1 and wave 2 demonstrate changing periodicity (mainly between two and 30 days) at different phases of the SSW event [20,21].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation